Revitalisasi Pendidikan Kuttab Di Era Digital - Nurhantanto, Armin; Nur'aini, Siti; Wachidi, Wachidi; Ali, Muhammad (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Kuttab education, as a traditional Islamic educational institution that has played an important role in educating generations of Muslims since medieval times, is now facing great challenges in the digital era. Advances in technology and changes in people's lifestyles have had a significant impact on the way of learning and teaching. This study aims to explore the revitalization efforts of Kuttab education in the face of digital transformation, focusing on curriculum adaptation, information technology utilization, and community involvement in the education process. The method used in this research is a qualitative approach with literature studies, interviews with educational practitioners, as well as direct observation in several Kuttab institutions that have begun to integrate digital technology in their learning process. The results showed that the revitalization of Kuttab in the digital era does not only involve updating teaching materials, but also the need to develop digital competencies for teachers and students. The use of digital learning platforms, Quran-based applications, and distance learning are some of the innovations that support the effectiveness of Kuttab education in this era. This study concludes that Kuttab education that integrates digital technology has great potential to expand access to quality Islamic religious education, while maintaining the traditional values that characterize Kuttab education.